A novel deletion in 2q24.1q24.2 in a girl with mental retardation and generalized hypotonia: a case report - Palumbo, Orazio (BioMed Central, 2012)
BACKGROUND: Chromosomal imbalances, recognized as the major cause of mental retardation, are often due to submicroscopic deletions or duplications not evidenced by conventional cytogenetic methods. To date, interstitial deletion of long arm of chromosome 2 have been reported for more than 100 cases, although studies reporting small interstitial deletions involving the 2q24.1q24.2 region are rare. With the widespread clinical use of comparative genomic hybridization chromosomal microarray technology, several cryptic chromosome imbalances have outlined new genotype-phenotype correlations and isolated a number of distinctive clinical conditions. RESULTS: here we report on a girl with mental retardation and generalized hypotonia. A genome-wide screen for copy number variations (CNVs) using single nucleotide polymorphisms (SNPs) array revealed a 7.5 Mb interstitial deletion of chromosome region 2q24.1q24.2 encompassing 59 genes, which was absent in parents. The gene content analysis of the deleted region and review of the literature revealed the presence of some genes that may be indicated as good candidate in generating the main clinical features of the patient. DISCUSSION: the present case represents a further patient described in the literature with an interstitial deletion of chromosome 2q24.1q24.2. Our patient shares some clinical features with the previously reported patients carriers of overlapping 2q24 deletion. Although more cases are needed to delineate the full-blown phenotype of 2q24.1q24.2 deletion syndrome, published data and present observation suggest that hemizygosity of this region results in a clinically recognizable phenotype. Considering these clinical and cytogenetic similarities, we suggest the existence of an emerging syndrome associated to 2q24.1q24.2 region.